6 Interpreting immune infiltrates and hormone biomarkers in young women with endometrial carcinoma (EC) through a moder lens (POST-TCGA) of molecular classification. (18th September 2019) - Farnell, D; Leung, S; Britton, H; Lum, A; Tessier-Cloutier, B; Huang, L; Shum, K; Kale, M; Yang, W; Kommoss, S; Brucker, S; Talhouk, A; et al.
Abstract : Objectives: Approximately 15% of ECs are diagnosed in women before the natural age of menopause. Fertility-sparing conservative management options are increasingly utilized, however biomarkers to inform prognosis or direct therapy are lacking. We sought to determine the value of additional immunohistochemical biomarkers in young women with EC in the context of modern TCGA-based molecular classification. Methods: Allred scores for estrogen/progesterone/androgen receptor and Ki67 in addition to immune characterization measuring stromal and epithelial expression of CD3/CD8/CD79a/CD138/PD1 and TIL high vs. TIL low clusters was performed in a cohort of previously characterized(n=257) young women (<50yo) with EC. Testing for association of biomarkers with clinicopathological parameters, ProMisE molecular subtype (mismatch repair deficient (MMRd), POLE mutated (POLE), p53wildtype (p53wt) and p53abnormal (p53abn)) and outcomes was performed. Results: Young women had a high proportion of immune-rich ECs: 80% TILhigh compared with 60% TILhigh in non-age stratified cohorts. Expression of all immune biomarkers was enriched within POLE and MMRd subtypes. Within MMRd and p53wt ECs TILhigh immune cluster was associated with improved overall-(OS)and disease-specific survival (DSS)(p<0.05 for all). High ER and PR expression was associated with low-grade ECs, and increased PD1 expression. A trend (LRT p-value 0.1) towards improved OS(HR 0.4) and DSS(HR 0.273) in high PR-expression ECs was observed. Inconsistencies in progesterone treatment (dose, duration) precluded our ability to make firm conclusions on PR thresholds and efficacy. In multivariable analysis only ProMisE subtype showed independent prognostic significance. Conclusions: Molecular classification with additional selective biomarker testing can provide additional prognostic information and may help stratify young women with ECs for targeted therapies.